Polyaniline Deposition on the Surface of Cotton Fibers: Structural Studies, Swelling Behavior, and Water Absorption Properties - Tesfamariam Teklu; Teklit Kidane Gebremedhin; Amanual Hadera Tesfay; Asfaw Gebretsadik Gebru; Ykalo Hadush Desta; Libargachew Demlie Mihretu; Hayal Lemma; Hiluf Hindeya Gebreyesus; Tadele Alemayo (Advances in Materials Science and Engineering)
Polyaniline-modified natural fibers have been recognized as promising candidates for conductive clothes, UV protection, and electromagnetic interference shielding. Hence, the purpose of this study was to investigate the effect of surface deposition of cotton fibers using polyaniline via in situ polymerization, and preceding structural changes were further screened by FT-IR, UV-Vis, TGA, SEM/EDX, and conductivity in comparison with bare cotton fibers used as the control sample. Polyaniline was introduced on the surface of cotton fibers as a conductive form, which was confirmed by electrical conductivity (1.54 × 10−4 Scm−1) equivalent to semiconductor materials. Detection of particular peaks at NKα 0.379 keV and ClKα 2.621 keV from EDX analysis revealed the introduction of nitrogen and chlorine, respectively. Polyaniline deposition on the cotton surface was successful to introduce hydrophobic environment to the system to enhance resistance to water absorption meaningfully.